Kajian Perumusan Permasalahan dan Isu Strategis Pembangunan Kabupaten Kotawaringin Timur Tahun 2021-2026 - Putra, Eki Darma (Al Makki Publisher, 2025)
Regional Development Problems are the cause of the gap between the development performance that is currently achieved and the planned one. Prioritizing strategic issues is carried out to determine the most priority strategic issues and will affect the formulation of missions, objectives, objectives, strategies and policy directions in the next five years. From the problems that have been studied, for the next 5 years of development, East Kotawaringin Regency has determined strategic development issues, namely: (1) Lack of Optimal Improvement of Human Resources Quality and Community Welfare, (2) Lack of Achievement of Bureaucratic Reform to Achieve Good Governance (3) Lack of Optimal Infrastructure Development, Fulfillment of Needs for Public Facilities and Facilities, and Increased Accessibility, (4) Sustainable Development and Resource Management Nature Optimally.